2011
DOI: 10.1016/s0973-6883(11)60234-x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Noncirrhotic Portal Hypertension in a Pediatric Population

Abstract: P ortal hypertension is classically caused by cirrhotic liver disease. However, there are several etiologies of portal hypertension that do not coincide with liver failure. Noncirrhotic portal hypertension may manifest clinically by upper gastrointestinal (GI) bleeding from esophageal varices, leukopenia, and thrombocytopenia from splenomegaly. 1,2 While studies have shown that certain liver functions are affected as a result of reduced portal venous flow, ascites and clinical encephalopathy are not common giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…(17) This finding differed from a study that analyzed 26 patients with noncirrhotic pHTN and found that the majority did well in the long term without surgical intervention. (3) In our study, the majority of patients who had an intervention underwent a transplantation and only a portion of these patients had a pre-operative gastrointestinal bleed. While variceal bleeding may be associated with confirmed gastrointestinal bleeding on endoscopy in patients with PRE who undergo a shunt, (10) it was a poor predictor for undergoing surgical intervention for pHTN in this study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…(17) This finding differed from a study that analyzed 26 patients with noncirrhotic pHTN and found that the majority did well in the long term without surgical intervention. (3) In our study, the majority of patients who had an intervention underwent a transplantation and only a portion of these patients had a pre-operative gastrointestinal bleed. While variceal bleeding may be associated with confirmed gastrointestinal bleeding on endoscopy in patients with PRE who undergo a shunt, (10) it was a poor predictor for undergoing surgical intervention for pHTN in this study.…”
Section: Discussionmentioning
confidence: 65%
“…While alcoholic, nonalcoholic steatohepatitis, and viral-induced cirrhosis are the most common causes of pHTN in adults in Western countries, intrahepatic (biliary atresia) and prehepatic (portal vein thrombosis) etiologies predominate in the pediatric population. (1)(2)(3)(4) A paucity of data in the literature exists regarding the outcomes and evidence-based management of pHTN in children, highlighting the need for further understanding of these variations.…”
mentioning
confidence: 99%
“…The current scoring system has been adopted from adult practice; however, it has not been validated in the literature 1,2,11. One retrospective study conducted in a single academic hospital setting found that the majority of patients with noncirrhotic portal hypertension did well long term without surgical shunt placements, and treatment focused mainly on surveillance and treatment of varices 12. However, this practice has not been well studied and reviewed in the literature 12…”
Section: Treatment and Managementmentioning
confidence: 99%